(untitled) (Physical Education, Health and Social Sciences, 2025)
A cross-sectional survey was undertaken among second to fifth-year undergraduate medical students at three Peshawar medical schools: Northwest School of Medicine, Rehman Medical College, and Pakistan International Medical College. Following informed consent and ethical approval, students completed a 15-item Likert scale comparing faculty-led instruction versus peer-assisted learning (PAL). Convenience sampling revealed that 262 of the 384 students who answered were qualified for the study. The anonymised data was analyzed in SPSS with descriptive statistics, paired-samples t-tests, independent t-tests, one-way ANOVA, and chi-square tests (p<0.05).The mean PAL score (Q1-Q15) was 1.62 (SD 0.51), while the average professor score (Q5-Q10) was 0.84 (SD 0.92). A paired t-test indicated that faculty-led teaching outperformed PAL (mean difference = -0.77, t = -19.81, p < 0.001). The preference numbers were: PAL = 214, Faculty = 47, and Equal = one. PAL perception varied by gender (male = 1.72 vs female = 1.46; t = 3.252, p = 0.0017) and college (ANOVA p < 0.001), with significant associations between preference and gender/college. In layman’s terms, students generally prefer PAL and peer-led learning, although they believe faculty-led education is more effective based on the metrics utilized. We suggest implementing structured, supervised peer-teaching programs with tutor training while maintaining faculty assistance. The study’s key flaws are its cross-sectional design (no causal claims), the exclusion of first-year students, the use of a self-created questionnaire, convenience sampling, and limited generalizability outside of the studied colleges.